How Emission Certificate Allocations Distort Fossil Investments: The German Example - Michael Pahle; Lin Fan; Wolf-Peter Schill (Energy Policy, 2011)
Despite political activities to foster a low-carbon energy transition, Germany currently sees a considerable number of new coal power plants being added to its power mix. There are several possible drivers for this "dash for coal", but it is widely accepted that windfall profits gained through free allocation of ETS certificates play an important role. Yet the quantification of allocation-related investment distortions has been limited to back-of-the envelope calculations and stylized models so far. We close this gap with a numerical model integrating both Germany's particular allocation rules and its specific power generation structure. We find that technology specific new entrant provisions have substantially increased incentives to invest in hard coal plants red to natural gas at the time of the ETS onset. More precisely, disproportionate windfall profits compared more than half the total capital costs of a hard coal plant. Moreover, shorter periods of free allocations would not have turned investors' favours towards the cleaner natural gas technology because of pre-existing economic advantages for coal. In contrast, full auctioning of permits or a single best available technology benchmark would have made natural gas the predominant technology of choice.
Additional information: This is a postprint of an article published in Energy Policy 39 (2011), 4, S. 1975-1987, available online at: http://dx.doi.org/10.1016/j.enpol.2011.01.027
Keywords: 330; Electricity sector investments; Windfall profits; ETS allocations; Energieökonomik; Emissionshandel; Allokation; Energiemarkt; Investition; Deutschland